Hubungan Faktor Lingkungan dan Praktik Pemberantasan Sarang Nyamuk (PSN) dengan Kejadian Demam Berdarah Dengue (DBD) di Kecamatan Ngawi - Luluk Masruroh; Nur Endah Wahyuningsih; Resa Ana Dina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Dengue Hemorrhagic Fever (DHF) was a disease caused infection by dengue virus. It transmitted through the bite of Aedes aegypti and Aedes albopictus. In 2015 according to Minister of Health Regulation No. 1501 / Menkes / Per / X / 2010 expressed as Extraordinary Events in Ngawi City. IR ( Incidence Rate) DBD District of Ngawi reached 59.9 per 100,000 population. Environmental and behavioral factors thought to be a risk factor for the cause of occurrence of dengue fever. The purpose of this study was to determine the correlation of environmental factors and mosquito eradication practice with incidence of Dengue Hemorrhagic Fever ( DHF) in the District of Ngawi. This study was observational analytic methods and case control design. The Case in this study were patients who visit Ngawi’s health centers and Ngawi Purba’s health centers on January to December 2015 which amounted to 154 ( cases ) and then the communities around cases within ± 100m from home cases to be a control. Statistical analysis used chi square test with proportional stratified simple random sampling. The results showed there were association between the presence of breeding place (p=0,0001 OR=9,6), the presence of vegetation (p=0,002 OR=6,01), Container Index ( CI ) (p=0,0001 OR=16,5), the practice of 3M (p=0,0001 OR=6,03), and the use of mosquito nets (p=0,001 OR=0,031) with the incidence of DHF. Based on these results the health center of Ngawi City collaboration with Ngawi’s health center and Ngawi Purba’s health center increase program outreach to the community about the practice of mosquito nest eradication and the promotion of larva monitoring as a precaution occurrence of dengue fever.